2001
DOI: 10.1139/o00-098
|View full text |Cite
|
Sign up to set email alerts
|

Identification of nuclear-import and cell-cycle regulatory proteins that bind to prothymosin α

Abstract: Prothymosin alpha (ProT alpha) is a nuclear protein that is widely distributed in mammalian tissues, and is thought to play a role in cell proliferation. In an attempt to shed light on this role, affinity chromatography on ProT alpha-Sepharose columns was used to identify proteins in subcellular extracts of transformed human lymphocytes (NC37 cells) that interact with ProT alpha in vitro, and thus may interact with ProT alpha in vivo. Immunoblotting techniques were used to screen the ProT alpha-binding fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 39 publications
1
9
0
1
Order By: Relevance
“…It is well accepted that prothymosin a concentrates mainly in the cell nucleus, while a small amount of the protein can be seen in the cytoplasm, and especially in perinuclear areas (Gomez-Marquez and Segade, 1998;Roson et al, 1990;Vareli et al, 1996;Rubtsov et al, 1997;Enkemann et al, 2000;Cotter and Robertson, 2000;Freire et al, 2001). The perinuclear concentrations of prothymosin a observed in this study (arrowead in Fig 3J) were found to be related to centrosomes/ microtubule organization centers (arrowead in Fig.…”
Section: Resultssupporting
confidence: 67%
“…It is well accepted that prothymosin a concentrates mainly in the cell nucleus, while a small amount of the protein can be seen in the cytoplasm, and especially in perinuclear areas (Gomez-Marquez and Segade, 1998;Roson et al, 1990;Vareli et al, 1996;Rubtsov et al, 1997;Enkemann et al, 2000;Cotter and Robertson, 2000;Freire et al, 2001). The perinuclear concentrations of prothymosin a observed in this study (arrowead in Fig 3J) were found to be related to centrosomes/ microtubule organization centers (arrowead in Fig.…”
Section: Resultssupporting
confidence: 67%
“…4). Because the thermally induced folding-unfolded profile of an oligomeric protein is dependent on the total protein concentration, the oligomerization state of a protein can be tested by carrying out DSC experiments at different protein concentrations (37). In the range of concentrations studied, the transition temperature of metal-free DtxR(C102D) is independent of the protein concentration, indicating that the protein behaves as a monomer.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that PTMA interacts with basic proteins, including histones, thanks to the acidic residues clustered in the central region of the molecule (Diaz-Jullien et al, 1996). In addition to this, PTMA also shares some aspects with SubH2Bv: it has a bipartite nuclear localization signal (-KR-X 12 -KKQK-) at its carboxy terminal (Rubtsov et al, 1997) but has been described in the cytoplasm too (Piñeiro et al, 2000); it binds to nuclear transport proteins, like Ran, karyopherine B, transportin (Enkemann et al, 2000;Freire et al, 2001) and participates in nuclear import pathways ( Karapetian et al, 2005;Niture and Jaiswal, 2009). All of these features suggest that PTMA may interact with PT proteins and, as a consequence, be directly involved in the pathways of acrosome assembly and acrosome-nuclear docking.…”
Section: Discussionmentioning
confidence: 99%